Investigating the Mediating Role of Brand Trust and Brand Engagement in the Relationship Between Social Media Marketing and Repurchase Intention: A Case Study of Coffee Shop Nyeduh Kopi - I Gede Bagus Dwijaya Dharmanatha; I Gst Ayu Kt. Giantari; Ni Nyoman Kerti Yasa; I Putu Gde Sukaatmadja; I Wayan Santika (International Journal of Management, Accounting & Finance (KBIJMAF), 2025)
This study investigates the mediating roles of brand trust and brand engagement in the relationship between social media marketing (SMM) and repurchase intention, using Coffee Shop Nyeduh Kopi in Tabanan as a case study. Grounded in the Stimulus-Organism-Response (SOR) model, this research explores how SMM, as an external stimulus, influences brand trust and brand engagement to drive repeat purchases. A quantitative approach was employed, collecting data through an online survey from 170 consumers of Coffee Shop Nyeduh Kopi. Data analysis was conducted using SEM-PLS via SmartPLS 3.0. Results confirm that SMM positively and significantly influences repurchase intention, brand trust, and brand engagement. Furthermore, both brand trust and brand engagement directly and positively affect repurchase intention. Crucially, brand trust and brand engagement were found to partially mediate the relationship between SMM and repurchase intention. These findings highlight the importance of cultivating brand trust and engagement through SMM to foster customer loyalty and repeat purchases.